Effect of planting density and nutrients on growth and seed yield of transplanted balsam (Impatiens balsamina) under Tarai conditions of Uttarakhand - PRABHAT KUMAR; VANDANA RAWAT; MEENAKSHI BASOLI; RAKESH MER; D.S. MISHRA (Seed Research, 2026)
The experiment was conducted at Model Floriculture Centre of GBPUA&T, Patnagar, Uttarakhand, during 2010, to evaluate vegetative and seed characters of balsam (Impatients balsamina Linn.) as affected by different agri-inputs. It was laid out in a split plot design with a spacing in main plot and nutrients in sub-plots. The main plot treatment consisted of three spacings 20 cm x 30 cm (S,), 30 cm x 30 cm (52), 40 cm x 40 cm (5,₂), whereas sub-plot treatments consisted of three levels of nitrogen (0, 15, 60 g/m²) and phosphorous (0, 15, 30 g/m²). Each treatment was replicated thrice. The application of 30 g N+30 g P/m² resulted in maximum number of primary branches, plant spread and 1,000-seed weight. Maximum number of secondary branches and seed yield were recorded with 30 g N+15 g P/m². Spacing of (30 cm x 30 cm) gave maximum number of primary branches, leaf area and seed yield. Number of secondary branches, plant spread and 1,000-seed weight were found to be highest under 40 cm x 40 cm spacing.